Meningkatkan Kemampuan Deteksi Risiko Kehamilan dan Persiapan Persalinan dengan Website Dan Buklet - Heny Rosiana; Rozikhan; Sayidah (Jurnal LINK, 2025)
The Maternal Mortality Rate is one of the indicators to assess the degree of public health, because of its sensitivity to improving health services, both in terms of accessibility and quality. The high maternal mortality rate is partly due to delays in early detection of the risk of complications. The purpose of this community service was to increase maternal knowledge in the prevention of complications and preparation for childbirth from the pregnancy period through the provision of health education based on booklets and websites. This community service method was health education and participatory discussions, with 13 pregnant women and 5 health cadres in Lebosari Village, Kangkung Kendal District. The activities carried out include health checks for pregnant women, provision of pre-tests of knowledge, education used website media and booklets, knowledge post tests, pregnancy exercises and oxytocin massage. The service was carried out once on June 25, 2025, and evaluation monitoring on August 30 and October 21, 2025. This activity increased the knowledge of pregnant women to detect early pregnancy conditions and hoped that pregnant women and cadres can find health information through the website or from booklets to increase knowledge about pregnancy, so that the sooner they recognize the risk of pregnancy, the better prepared they can face childbirth, including the ability to recognize emergency situations so that mothers can be referred to higher health service facilities when they occur Complications.